2016
DOI: 10.4103/0972-5229.180047
|View full text |Cite
|
Sign up to set email alerts
|

Severe subcutaneous emphysema and pneumomediastinum secondary to noninvasive ventilation support in status asthmaticus

Abstract: A 12-year-old male with status asthmaticus developed subcutaneous emphysema and pneumomediastinum. He was transferred to our unit, where he received noninvasive ventilation (NIV). This respiratory support technique is not an absolute contraindication in these cases. After 2 h on NIV, he worsened sharply and the subcutaneous emphysema got bigger suddenly. He needed invasive ventilation for 5 days. Final outcome was satisfactory. This case illustrates that it is mandatory to keep a high level of vigilance when u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 11 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…Despite frequent use of NIV for acute respiratory failure due to varied causes, SE is very seldom reported with its use in literature [ 12 , 13 ] before COVID-19. It is therefore postulated that COVID-19 patients with extensive lung damage might have increased respiratory drive with persistent strong spontaneous inspiratory efforts causing self-inflicted lung injury as postulated by Gattinoni [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite frequent use of NIV for acute respiratory failure due to varied causes, SE is very seldom reported with its use in literature [ 12 , 13 ] before COVID-19. It is therefore postulated that COVID-19 patients with extensive lung damage might have increased respiratory drive with persistent strong spontaneous inspiratory efforts causing self-inflicted lung injury as postulated by Gattinoni [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“… 13 Gonzalez and colleagues (2016) reported a case of NIV induced exacerbation of air leak resulting in intense cervical subcutaneous emphysema and pneumomediastinum in a patient with asthma. 2 SE can occur without pneumothorax or pneumomediastinum in patients with cavitary pulmonary tuberculosis. 14 Singh and colleagues reported a case of spontaneous SE and pneumomediastinum in a patient with H1N1 pneumonia.…”
Section: Discussionmentioning
confidence: 98%
“…Cases of NIV induced pneumomediastinum and subcutaneous emphysema (SE) have been reported in patients with chronic obstructive pulmonary disease (COPD) and asthma. 2 Recently a few authors have also reported this in Covid-19 patients. 3 , 4 In this communication we report an occurrence of bilateral subcutaneous emphysema in a patient of COVID-19 pneumonia without pneumothorax and pneumomediastinum having no previous history of respiratory disease.…”
Section: Introductionmentioning
confidence: 85%
“…1 The prevalence of ES varies from 0.43% to 2.34%. [2][3][4] A study conducted by Aghajanzadeh et al over a period of 10 years revealed that the mean age of those diagnosed with ES ranges from 25 to 53 years, with males accounting for 71% of the patient population.…”
Section: Introductionmentioning
confidence: 99%